Nitrogen-doped carbon nanotubes as efficient catalysts for isobutane dehydrogenation. Issue 24 (24th November 2016) - Mu, Jiali; France, Liam John; Liu, Baoan; Shi, Junjun; Long, Jinxing; Lv, LuFeng; Li, Xuehui
Abstract : Large-scale production of isobutene from isobutane requires high-performance and cost-effective catalysts. Abstract : Large-scale production of isobutene from isobutane requires high-performance and cost-effective catalysts. Carbon-based nanomaterials such as carbon nanotubes have attracted great attention as substrates for decorating with functional groups or doping with heteroatoms. In this paper, oxidized multi-walled carbon nanotubes were modified with nitrogen at 900 °C and applied in direct dehydrogenation of isobutane. Upon surface oxidization and high temperature annealing, the 1.93 atom% nitrogen-doped oxidized multi-walled carbon nanotubes are found to be an effective dehydrogenation catalyst, which exhibits an isobutane conversion of 51.8% (17.4 mmol g −1 h −1 ), isobutene selectivity and yield of 45.9% and 23.8% (8.0 mmol g −1 h −1 ) respectively. The increased catalytic performance is well-correlated with enhanced adsorption strength of isobutane and reduced adsorption strength of isobutene, which relates to the presence of nitrogen species, as revealed by XPS and TPD measurements. Minimal deactivation of the catalyst, as indicated by time on stream studies, may be caused by the loss of nitrogen heteroatoms and the change in I D / I G .